Nauczanie języka polskiego na uniwersytecie w Wielkim Tyrnowie - Dankowa, Steliana (Postscriptum Polonistyczne, 2020)
This article presents teaching Polish as a foreign language at the University of Veliko Turnovo. The author analyses the difficulties that students have in learning the Polish language, highlighting the differences between the Polish and Bulgarian language and common mistakes that students make. She also describes teaching methods.